2023
DOI: 10.2147/jir.s400233
|View full text |Cite
|
Sign up to set email alerts
|

High Infiltration of CD203c+ Mast Cells Reflects Immunosuppression and Hinders Prognostic Benefit in Stage II-III Colorectal Cancer

Abstract: Background Activated mast cells (AMCs) have been fully researched in inflammation and allergic reactions. However, the protumoral role of AMCs and their biomarker CD203c has not yet been investigated in colorectal cancer (CRC). Methods We retrospectively collected 449 postoperative patients with stage II–III CRC at two different hospitals as the training (n=310) and validation (n=139) cohorts. These findings were further validated in the independent cohort (Integration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Li et al found a significant enrichment of immunosuppressive angiogenesis pathways in CRC with high infiltration of activated mast cells. This infiltration was inversely correlated with CD8+ T-cell infiltration, suggesting that high activated mast cell infiltration in the CRC microenvironment may be associated with an immunosuppressive phenotype [34]. Thus, the downregulation of TET2 expression in CRC may lead to an increased infiltration of immune suppressive cells, contributing to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al found a significant enrichment of immunosuppressive angiogenesis pathways in CRC with high infiltration of activated mast cells. This infiltration was inversely correlated with CD8+ T-cell infiltration, suggesting that high activated mast cell infiltration in the CRC microenvironment may be associated with an immunosuppressive phenotype [34]. Thus, the downregulation of TET2 expression in CRC may lead to an increased infiltration of immune suppressive cells, contributing to a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Mast cell infiltration in tumours has recently been reported [ 27 , 28 ]; unfortunately, the phenotypic characteristics of mast cells and their functions are still poorly understood. Many immune coinhibitory signals are associated with immunosuppression in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…[ [53][54][55][56][57][58][59][60] Breast Cancer • MCs play pivotal roles, influencing tumor immune regulation, angiogenesis, and metastatic progression.…”
Section: Gastric Tumormentioning
confidence: 99%
“…However, the precise role of MCs in colorectal cancer remains a subject of controversy. Some studies suggest that MCs may promote tumor development [57,58], while others propose that they might have anti-tumor properties [59]. This controversy stems from the multi-functionality and complexity of MCs, exhibiting differential behavior in various stages and types of colorectal cancer [60].…”
Section: Gastric Tumormentioning
confidence: 99%